Global Character of a Six-Dimensional Nonlinear System of Difference Equations - Mehmet Gümüş; Yüksel Soykan (Discrete Dynamics in Nature and Society)
The aim of this paper is to study the dynamical behavior of positive solutions for a system of rational difference equations of the following form: un+1=αun-1/β+γvn-2p, vn+1=α1vn-1/β1+γ1un-2p, n=0,1,…, where the parameters α,β,γ,α1,β1,γ1,p and the initial values u-i,v-i for i=0,1,2 are positive real numbers.